Microdomain orientation dependence on thickness in thin films of cylinder-forming PS-b-PMMA - Zucchi, Ileana Alicia (2010)
The self-assembly of block-copolymer thin films in periodic nanostructures has received considerable attention during the last decade due to their potential applications in nanofabrication and nanolithography. We followed the morphologies developed in thin films of a cylinder-forming diblock copolymer polystyrene-b-poly(methylmethacrylate) ((PS-b-PMMA), PS 46.1 kg mol−1, PMMA 21.0 kg mol−1, lattice spacing L0 = 36 nm), as a function of the film thickness (t), analyzing the effect of thickness commensurability on domain orientation in respect to the substrate. The study was circumscribed to the unexplored range of thickness below L0. Two thickness windows with perpendicular orientation of the PMMA domains were identified: a well-known window at t ~ L0 and a new window at t ~L0/2. A half-parallel cylinder morphology was observed for t ~ ¾ L0 with a progressive change in morphology C┴ → C|| → C┴ when thickness increases from L0/2 to L0. This experimental evidence provides new insights on the mechanism of block copolymers self-organization and indicates the possibility to tune the thickness of the nanostructured polymeric film below L0, allowing the fabrication of ultrathin soft masks for advanced lithographic processes.